2020
DOI: 10.21203/rs.3.rs-43538/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards unravelling Wolbachia global exchange: a contribution from the Bicyclus and Mylothris butterflies in the Afrotropics

Abstract: Background Phylogenetically closely related strains of maternally inherited endosymbiotic bacteria are often found in phylogenetically divergent, and geographically distant insect host species. The interspecies transfer of the symbiont Wolbachia has been thought to have occurred repeatedly, facilitating its observed global pandemic. Few ecological interactions have been proposed as potential routes for the horizontal transfer of Wolbachia within natural insect communities. These routes are however likely to ac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 48 publications
(75 reference statements)
1
9
1
Order By: Relevance
“…Most of the Wolbachia STs detected in butterflies in this study (14 species, 88%) belonged to supergroup B, whereas those found in Ypthima praenubila Leech and Ypthima spec. (Nymphalidae) belonged to supergroup A, similar to previous studies (e.g., Ahmed et al, 2016;Ilinsky & Kosterin, 2017;Duplouy et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Most of the Wolbachia STs detected in butterflies in this study (14 species, 88%) belonged to supergroup B, whereas those found in Ypthima praenubila Leech and Ypthima spec. (Nymphalidae) belonged to supergroup A, similar to previous studies (e.g., Ahmed et al, 2016;Ilinsky & Kosterin, 2017;Duplouy et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…The infection incidence in our collection was lower than reported elsewhere (Tagami & Miura, 2004;Salunke et al, 2012;Ilinsky & Kosterin, 2017;Duplouy et al, 2020). Possibly, the actual percentage of Wolbachia infection is higher than estimated, due to the relatively small sample size for some butterfly species and populations.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations